Effect of CD34+ cell dose on hematopoietic reconstitution and outcome in 508 patients with multiple myeloma undergoing autologous peripheral blood stem cell transplantation - Klaus, Jens; Herrmann, Doris; Breitkreutz, Iris; Hegenbart, Ute; Mazitschek, Uta; Egerer, Gerlinde; Cremer, Friedrich Walter; Lowenthal, Ray M.; Hüsing, Johannes; Frühauf, Stefan; Möhler, Thomas; Ho, Anthony Dick; et al. (European journal of haematology, 2007)
Background: We analyzed the hematopoietic reconstitution and outcome of 508 patients with multiple myeloma (MM) with respect to the number of CD34+ cells reinfused at our center. Patients and methods: Each cohort of 390 patients (unselected CD34+ cell transplant) and 118 patients (CD34+ selected transplant) was divided into four subgroups. Among the 390 transplantations, 86 patients received a high dose (HD−) of ≥6.50 × 106 unselected CD34+ cells/kg, 116 patients a low dose (LD−) of <3.00 × 106 CD34+ cells/kg. Among the patients treated with CD34+ selected PBSC, 34 received ≥6.50 × 106 CD34+ cells/kg (HD+) and 16 <3.00 × 106 CD34+ cells/kg (LD+). Results: HD− patients experienced a reduced median time to leukocyte (13 d vs. 14 d) (P < 0.001) and platelet reconstitution >20 × 109/L (10 d vs. 12 d) (P < 0.001). Similarly, HD+ showed a reduced median time to leukocyte (12 d vs. 15 d) (P < 0.001) and platelet recovery >20 × 109/L (10 d vs. 11 d) (P = 0.058). CD34+ cell-dose was significant for long-term platelet recovery at day 360 (unselected transplant P = 0.015, selected transplant P = 0.023). Number of transplanted CD34+ cells had no significant impact on transplant related mortality, overall survival or CR/PR rates within 100 d. In terms of supportive care the differences of high-/low-dose grafts were minimal. Conclusions: These results confirm that high doses of CD34+ PBSC shorten hematopoietic reconstitution and reduce hospitalization. Nevertheless secure engraftment results from transplantation of 2.00-3.00 × 106 CD34+ cells/kg. As 60% of our pretreated patients are able to collect ≥5.00 × 106 CD34+ cells/kg within a single leukapheresis, division into two or more freezing bags allows safe tandem transplantation in the majority of MM patients.
Das Pluszeichen im Titel ist hochgestellt
Frontdoor: First published: 22 November 2006
Gesehen am 26.10.2021